2019
DOI: 10.3390/ma12234020
|View full text |Cite
|
Sign up to set email alerts
|

Composite Eco-Friendly Sound Absorbing Materials Made of Recycled Textile Waste and Biopolymers

Abstract: In recent years, the interest in reusing recycled fibers as building materials has been growing as a consequence of their ability to reduce the production of waste and the use of virgin resources, taking advantage of the potential that fibrous materials may offer to improve thermal and acoustic comfort. Composite panels, made of 100% wool waste fibers and bound by means of either a chitosan solution and a gum Arabic solution, were tested and characterized in terms of acoustic and non-acoustic properties. Sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 47 publications
(50 reference statements)
2
30
0
Order By: Relevance
“…[ 6 ] Multiple studies detailed textile waste‐reinforced composites as a replacement of wood or wood particle boards. Rubino et al [ 22 ] reported composite materials made of wool fibers extracted from waste woolen textiles and chitosan and gum arabic for thermal and sound insulation applications for the building industry. Temmink et al [ 23 ] studied composites reinforced with denim jeans fabric waste.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Multiple studies detailed textile waste‐reinforced composites as a replacement of wood or wood particle boards. Rubino et al [ 22 ] reported composite materials made of wool fibers extracted from waste woolen textiles and chitosan and gum arabic for thermal and sound insulation applications for the building industry. Temmink et al [ 23 ] studied composites reinforced with denim jeans fabric waste.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Rubino et al [ 64 ], composite panels have been made from wool waste fibers in the form of cut fabrics, bound through two different polysaccharides: a chitosan solution from crustacean by-products, and a gum Arabic solution from the Acacia tree. The material has been designed for potential building construction by experimenting with the sound absorbing and thermal insulating properties.…”
Section: Recent Applications Of Waste Textiles Into Organic or Inomentioning
confidence: 99%
“…Thus, based on the results of various tests, the authors in [ 3 ] stated that their researched textile waste fibers can be incorporated into mortars, thereby replacing sand and cement by volume and adding advantages, such as improved cracking behavior. The authors in [ 4 ] investigated the performance of composite materials obtained from the use of fibers derived from recycled textile wastes (100% merino wool), combined with different binders, to be used as building materials with sound absorption and thermal insulation properties. The results confirmed that such materials have similar or better performance than conventional thermal insulating and sound-absorbing materials.…”
Section: Introductionmentioning
confidence: 99%